The Cost of Link Layer Security in IoT Embedded Devices ⁎. Issue 6 (2018) - Alharby, S.; Weddell, A.; Reeve, J.; Harris, N.
Abstract: Security of Internet of Things (IoT) devices is important for the acceptance of IoT applications. Several security mechanisms have been proposed, however, due to the limited resources in IoT devices, their overhead should be evaluated carefully. Many existing security solutions have been evaluated by simulation. However, with the increasing deployment of real nodes, a more accurate result based on real hardware is necessary. This research aims to evaluate the impact of applying security features of IEEE 802.15.4 on example hardware. The evaluation includes the impact on the Microcontroller Unit (MCU), radio, latency, packet throughput and transmission power. The results show that enabling software security services impact limited devices significantly. This impact could be translated into a decrease in throughput to almost 44%, an increase in latency and energy consumption to almost 197% and 86% respectively with maximum security level. The outcome of this paper is intended to benefit network designers and researchers by allowing them to model security overhead, allowing them to choose the security level, if enabled, which suits their application requirements.